Microexplosive Atomization of Heterogeneous Fuel Drops for Intensifying Their Ignition; Chemical and Petroleum Engineering; Vol. 55, iss. 7-8 - Antonov D. V. Dmitry Vladimirovich; Nyashina G. S. Galina Sergeevna; Fedorenko R. M. Roman Mikhaylovich; Filatova A. S. Anastasiya Stanislavovna (2019, 2019)
Title screen